PENGARUH MODEL PEMBELAJARAN AUDITORY, INTELLECTUALY, REPETITION BERBANTUAN MEDIA AUDIO VISUAL TERHADAP KOMPETENSI PENGETAHUAN IPA - ayu Yunita Dewi (Universitas Pendidikan Ganesha, 2018)
This research was aimed at determining the significant differences regarding knowledge competence of science between groups of students applying auditory, intellectualy, repetition learning model using audio visual media with group of students who applied conventional learning in grade IV of SD Gugus Kompyang Sujana in North Denpasar, academic year 2017/2018. The type of research used was quasi experiment by using non-equivalent group design. The population of this study were 346 students covering all the fourth graders of SD Gugus Kompyang Sujana in North Denpasar, academic year 2017/2018. Sampling was done by group sample technique, which was held by doing random in class group, so that the following results were obtained; IVA grade of SD Negeri 4 Tonja as experiment class and IV grade of SD Negeri 4 Peguyangan as control class. The result of calculation of